DIFFERENT APPROACH FOR Management OF HYPERTENSION EMERGENCY AND URGENCY AMONG EMERGENCY PHYSICIANS AND OTHER SPECIALISTS IN THE ITALIAN REAL WORLD. (April 2021) - Saladini, Francesca; Mancusi, Costantino; Maloberti, Alessandro; Giavarini, Alessandra; Bertacchini, Fabio; Spannella, Francesco; Rosticci, Martina; Bruno, Rosa Maria; Pucci, Giacomo; Pengo, Martino; Grassi, Davide; Muiesan, Maria Lorenza
Abstract: Objective: To investigate differences for management and treatment of hypertension emergency (HE) (HU) and urgency among emergency physician and doctors working in other departments. Design and method: The young investigator research group of the Italian Society of Hypertension developed a 23-item questionnaire spread by E-mail invitation to the members of Italian Scientific societies in the field of Emergency Medicine and Hypertension. Results: 665 questionnaires were collected: 59.7% from emergency departments (EDs), 22% from Emergency and Urgency Medicine wards, 8.7% from Cardiology Units, 5.7% from Internal Medicines and 3.9% from Intensive care or Stroke units. Emergency physicians more frequently defined chest pain as possible presentation of HE than other physicians (91.2 % vs 85.8% p < 0.05), while tinnitus and conjunctival hemorrhages were less frequently considered as possible presenting symptoms (35% vs 42.9%, p < 0.05 for tinnitus; 38.5% vs 45.9% p = 0.05 for conjunctival hemorrhages). We did not observe any significant differences in most of laboratory and instrumental examinations, except for lung ultrasound that was most frequently performed by emergency physicians compared the other specialists (43.8% vs 32.1% p < 0.005). They also investigated cocaine or amphetamine abuse more frequently than the others (98.5% vs 95.9% p < 0.05). The therapeutic approach for blood pressure (BP) reduction showed some differences: a larger use of urapidil (67.8% vs 54.9% p = 0.003) and captopril (59.6% vs 39.2 % p = 0.002) and lower of furosemide (54.4% vs 66.8% p < 0.05) was reported by ED physicians compared to other groups. Hospitalization was more frequently required in the presence of acute organ damage (45.3% vs 30% p < 0.05) by emergency physicians than other specialists, on the opposite side they suggested less frequently hypertension specialist evaluation (63% vs 74% hypertension specialist advice in more than 50% of cases, p < 0.05) and ambulatory BP monitoring (65% vs 79% p = 0.001) or home self BP monitoring (39.4% vs 56.1% in at least the 75% of cases, p = 0.003) than the other specialists. Conclusions: Management and treatment of HE and HU may be different according to doctor's specialty. Educational initiatives, should be done to standardized treatment protocols and to improve medical knowledge about this largely prevalent problem.